Aesthetics of Topeng Getak Dance in Feature Dance Festival by Students of SMPN 3 Pamekasan - Roro Jamila (PT Inovasi Penelitian Terpadu, 2025)
Getak Mask Dance is a superior dance from Pamekasan Regency, to participate in the Getak Mask Dance Festival for Junior High Schools throughout the regency, students of SMP Negeri 3 Pamekasan managed to get 5 best presenters from 17 junior high schools throughout the regency. This article aims to find out and describe the beauty of body language in junior high school dancers when dancing the Getak Mask Dance with the concept of Mataram Joged Philosophy which contains elements of sawiji, greged, sengguh, and ora mingkuh. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study showed that sawiji or the unity of the dancers with the character of the Baladewa figure with the right mask delivery. Solidarity and body language are the impact of character unity. Greged which is typical of the Getak Mask dance delivery can be mastered by them. Although there is still one dancer out of three dancers who is not fully sengguh, it can be covered by the compactness of the dancers in performing the dance. The determination of the dancers who concentrate totally and have full responsibility for the dance being performed makes the Topeng Getak Dance have a strong body language aesthetic in accordance with the philosophical concept of Joged Mataram.